2018
DOI: 10.14295/cs.v9i1.1313
|View full text |Cite
|
Sign up to set email alerts
|

Initial development of Physalis seedlings in substrates and containers

Abstract: The objective of this study was to evaluate the growth of Physalis peruviana and Physalis pubescens in containers and substrates, as well as the growth of transplanted P. pubescens seedlings into different containers and substrates. It was used for transplanting experiment (E1) plastic bags, disposable plastic glasses and plastic tubes containing four substrates: oxisol; commercial substrate; commercial substrate + fine washed sand; and commercial substrate + oxisol + fine washed sand. For the experiment of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The lower plant height grown in the 50 cm 3 pool is probably due to the lower volume of substrate due to the limited space available, restricting the expansion of the root system, which consequently results in low nutrient availability, making plant development difficult. Costa et al (2011) and Oliveira et al (2011) working with the production of eggplant and tomato seedlings respectively, also found that the volume of the pool has a direct relationship with the height of the plants, since the seedlings that had the highest heights were grown in the largest containers. Note.…”
Section: Resultsmentioning
confidence: 96%
“…The lower plant height grown in the 50 cm 3 pool is probably due to the lower volume of substrate due to the limited space available, restricting the expansion of the root system, which consequently results in low nutrient availability, making plant development difficult. Costa et al (2011) and Oliveira et al (2011) working with the production of eggplant and tomato seedlings respectively, also found that the volume of the pool has a direct relationship with the height of the plants, since the seedlings that had the highest heights were grown in the largest containers. Note.…”
Section: Resultsmentioning
confidence: 96%